Modelling of heat and mass transfer from spheroidal drops with non-uniform surface temperature. (June 2018) - Tonini, Simona; Cossali, Gianpietro Elvio
Highlights: Effect of non-uniform surface temperature on drop heat and mass transfer. Heat and mass transfer modelling of single-component spheroidal drops. Analytical/numerical coupled solution of species/energy conservation equations. Effect of temperature disuniformity on local and global heat transfer coefficient. Abstract: The heating and evaporation of single component spherical and spheroidal (oblate and prolate) drops in gaseous quiescent environment are modelled, accounting for the effect of a non-uniform distribution of the temperature at the drop surface. The analytical solution to the species conservation equations in the proper coordinate system (spherical/spheroidal) is used to numerically solve the energy equation. The effect of temperature disuniformity on the local non-dimensional heat transfer coefficient and global heat and evaporation rates is calculated for different drop temperature disuniformity, mean surface temperature, drop deformation, gas temperature and pressure and liquid species.